KECEPATAN LELEH, pH DAN KADAR GLUKOSA ES KRIM SUSU KAMBING DENGAN BAHAN PENSTABIL GEL DAUN CINCAU HIJAU (Cyclea barbata Miers) PADA KONSENTRASI BERBEDA - Sofyan Hidayat; Wieda Nurwidada H Z; Bambang Kuntoro (Jurnal Peternakan, 2019)
This research was conducted in May to June, 2016 in Post-Harvest Technology Laboratory of the Faculty of Agriculture and Animal Science State Islamic University of Syarif Kasim Sultan Riau, and Laboratory of Food and Beverage Trade, Cooperatives, Small and Medium Enterprises Services, Pekanbaru City, Riau Province. This study of aims to determine the physical quality the ice cream with the addition of grass jelly leaves gel as a stabilizer in ice cream. The experimental design used in this study was completely randomized design with five treatments and four replications. Parameters obsered were on study treatment is P0 (without grass jelly leaves gel), P1 (0,25% of grass jelly leaves gel), P2 (0,50% of grass jelly leaves gel), P3 (0,75% of grass jelly leaves gel) and P4 (1,00% of grass jelly leaves gel). The parameters observed were melting time, pH and glucose content. The results showed that the addition of grass jelly leaves gel did not significantly affect (P>0.05) melting rate of ice cream, but significantly decreased the pH value of ice cream (P<0.01) and increased glucose concentration of goat milk ice cream (P<0.01). The conclusions of this research that goat milk ice cream stabilized using grass jelly leaves gel at the level of 1,00% produce yield glucose content was 38,91%, the melting rate for 13,45 minutes and 6,10 of pH value